Design and Evaluation of Cascode GaN FET for Switching Power Conversion Systems. Issue 1 (1st February 2017) - Jung, Dong Yun; Park, Youngrak; Lee, Hyun Soo; Jun, Chi Hoon; Jang, Hyun Gyu; Park, Junbo; Kim, Minki; Ko, Sang Choon; Nam, Eun Soo
Abstract : In this paper, we present the design and characterization analysis of a cascode GaN field‐effect transistor (FET) for switching power conversion systems. To enable normally‐off operation, a cascode GaN FET employs a low breakdown voltage (BV) enhancement‐mode Si metal‐oxide‐semiconductor FET and a high‐BV depletion‐mode (D‐mode) GaN FET. This paper demonstrates a normally‐on D‐mode GaN FET with high power density and high switching frequency, and presents a theoretical analysis of a hybrid cascode GaN FET design. A TO‐254 packaged FET provides a drain current of 6.04 A at a drain voltage of 2 V, a BV of 520 V at a drain leakage current of 250 μA, and an on‐resistance of 331 mΩ. Finally, a boost converter is used to evaluate the performance of the cascode GaN FET in power conversion applications.